Raw materials price rise easing off - Heinz Kolbe (Intereconomics, 1989)
Due to the slow-down in the worldwide increase in business activity, the growth of demand for raw materials is expected to decelerate. Production, on the other hand, will continue to increase rapidly.
Keywords: 330